ROSALIE RAHAL HADDAD, Bernard Shaw in Brazil. The Reception of Theatrical Productions, 1927-2013 - Murphy, Maureen (ABEI Journal, 2017)
ROSALIE RAHAL HADDAD, Bernard Shaw in Brazil. The Reception of Theatrical Productions, 1927-2013. Bern: Peter Lang, 2016. 276 pp.